A Mensa Book of Brain Teasers - Alan Wareham (Orient Paperbacks, 1993)
Mensa is an organization for people with a high level of brain power. It does not matter whether you are a housewife, student, researcher, businessman or teacher, you can still be a part of Mensa if you are able to stand in the top 2 percent after the standard test. Mensa Book of Brain Teasers by Alan Wareham consists of several brain challenging puzzles and problems to tickle your mind. The book starts with a chapter on warm-ups which prepares you for what is to come and consists of problems like number of squares in a diagram etc. Other puzzles that follow include anagrams, logic, numbers and word-related problems. Power puzzles are the hardest in the book and are hard to solve without the use of a calculator or some previous scientific knowledge. Mensa Book of Brain Teasers is a useful tool for those who are looking to sharpen their mind. You need not become a member of Mensa but instead aspire to be quick and smart about logical problems that you come across in your daily scenarios. The problems in the book are hard to decipher as their standards are high and all of them require intelligence and quick-thinking. Mensa Book of Brain Teasers was published by Orient Paperbacks in 2006 and is available in paperback. Key Features: The book contains a separate section on complex crossword puzzles . At the end of the book, there are answers for several of the previously-stated puzzles and problems.